Pengelolaan Surat Berbasis Elektronik Pada Lembaga Pendidikan - Darmansyah, Tengku; Salsabila , Salwa; Pradita, Syakila; Panjaitan, Azhari; Siregar, Mustofa; Sagala, Ardin Andre Rizki (CV. ITTC INDONESIA, 2024)
An increasingly advanced, modern and sophisticated era is developing because of human needs and problems that encourage creativity and innovation. Good management of correspondence in government agencies is very important because good management of correspondence will help communicate information and communication to agencies which is a determining factor in development policies and strategies. The aim of this research is to develop an effective and efficient electronic mail management system in educational institutions, as well as determine its impact on the mail management process and service quality in educational institutions. The research studied is qualitative research using the literature review method. Literature review by utilizing information from secondary data from various published research articles. This secondary data was used as review material for a number of articles, originating from international and national scale articles. The results of this research are that the electronic letter management system includes the activities of creating, recording and organizing letters which are stored on hardware and then organized using software and controlled by the user or brainware. Implementing an electronic mail management system in educational institutions also requires training so that employees can be skilled in using it. Management of electronic incoming mail at educational institutions, namely receiving, sorting, recording, distributing and storing. Management of electronic outgoing mail, namely the concept of letters, typing, signing, recording, sending and storing letters.